The environments of the poor in southeast Asia, East Asia, and the Pacific (Institute of Southeast Asian Studies, 2013)
This book provides examples of possible triple-win solutions for simultaneously reducing poverty, raising the quality of the environment, and adapting to climate change. The book provides empirical evidence and observations from sixteen case studies in Southeast and East Asia, and from the Pacific. It argues that a spatial approach focussing on the environments in which the poor and vulnerable live, would trigger changes for development policies and implementation that better balance environmental and social concerns. In line with the post-2015 Millennium Development Goals (MDG) and Sustainable Development Goals (SDG) agenda, emphasizing integrated development approaches for the slum poor, the upland poor, the dryland poor, the coastal poor, and the flood-affected wetland poor, would also bring the environment and poverty agenda closer.